2011
DOI: 10.1002/hep.24509
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of hepatic growth hormone and glucocorticoid receptor signaling causes steatosis and hepatocellular carcinoma in mice

Abstract: Growth hormone (GH)-activated signal transducer and activator of transcription 5 (STAT5) and the glucocorticoid (GC)-responsive glucocorticoid receptor (GR) are important signal integrators in the liver during metabolic and physiologic stress. Their deregulation has been implicated in the development of metabolic liver diseases, such as steatosis and progression to fibrosis. Using liver-specific STAT5 and GR knockout mice, we addressed their role in metabolism and liver cancer onset. STAT5 single and STAT5/GR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(130 citation statements)
references
References 47 publications
(75 reference statements)
5
125
0
Order By: Relevance
“…Moreover, the presence of the Cre transgene in GR AlfpCre mice does not lead to hepatic steatosis and up-regulation of genes involved in hepatic lipid synthesis and uptake. 1 Second, our data resemble findings published by the Hennighausen laboratory, which report that Stat5 deletion causes hepatic steatosis and carcinoma formation using Alb-Cre mice. 2,3 Additionally, we examined body weights of 2-month-old Stat5 loxP/loxP ;GR loxP/loxP ;Tg:AlfpCre/0, Stat5 flox/1 ;GR loxP/1 , and Stat5 loxP/1 ;GR loxP/1 ; Tg:AlfpCre/0 male littermates.…”
Section: Replysupporting
confidence: 88%
“…Moreover, the presence of the Cre transgene in GR AlfpCre mice does not lead to hepatic steatosis and up-regulation of genes involved in hepatic lipid synthesis and uptake. 1 Second, our data resemble findings published by the Hennighausen laboratory, which report that Stat5 deletion causes hepatic steatosis and carcinoma formation using Alb-Cre mice. 2,3 Additionally, we examined body weights of 2-month-old Stat5 loxP/loxP ;GR loxP/loxP ;Tg:AlfpCre/0, Stat5 flox/1 ;GR loxP/1 , and Stat5 loxP/1 ;GR loxP/1 ; Tg:AlfpCre/0 male littermates.…”
Section: Replysupporting
confidence: 88%
“…GH in turn targets the liver in a sexspecific manner, which is particularly evident in rodents at puberty, but is also found in humans 90 . GH function is mediated by the transcriptional activator STAT5, which can protect hepatocytes from chronic injuries and malignant transformation 12 , providing another possible mechanism for sexual dimorphism in HCC development.…”
Section: Sex Hormone Signaling In Specific Cancer Typesmentioning
confidence: 99%
“…In both prior works, reduced hepatic GR activity also resulted in hypercortisolism due to compensation by the hypothalamic-pituitary-adrenal (HPA) axis in response to peripheral glucocorticoid insensitivity. Liver-specific GR-knockout mice also display increased corticosteroid-binding globulin, which keeps the circulating GCs in an inactive form, thereby further inducing compensatory activation of the HPA axis (46). In Cushing's disease, hypercortisolism commonly leads to hepatic steatosis (53).…”
Section: Glucocorticoid Receptor and Fatty Livermentioning
confidence: 99%
“…These facts suggest that GC overstimulation may also contribute to steatosis. Indeed, Mueller et al (46) demonstrated that hypercortisolism due to GR deletion from hepatocytes caused increased GR activation in adipocytes, which consequently led to increased lipolysis via upregulation of ATGL and HSL and reduction of perilipins. This phenomenon ultimately results in the overall diminution of adipose storage and the subsequent elevation of circulating FFAs, which accumulate in the liver (46).…”
Section: Glucocorticoid Receptor and Fatty Livermentioning
confidence: 99%